RUSSIA IS RISING: TRADITIONALISM OF DRAGOŠ KALAJIĆ AND THE RESTORATION OF THE EMPIRE - Gajic, Aleksandar (Political Review, 2025)
Dragoš Kalajić, a painter, publicist, and writer, represents one of the most distinctive and controversial figures in the Serbian public during the last three decades of the 20th and the beginning of the 21st century. The Paper deals with Kalajić’s essays on Russia during the collapse of the Soviet Union as well as the period of Yeltsin’s Russia, with a special emphasis on his assessments of the state of Russian society, its capacities for renewal and growth into a state that will have the strength to once again play a major role in world politics in the 21st century. The first part of the Paper provides a brief overview of Kalajić’s public activity, primarily referring to his basic biographical and bibliographical data. The second part of the Paper explains Kalajić’s attitude towards Russia, the visits and activities he developed there during the 80s and 90s of the 20th century, as well as the influence he left on the Russian public and cultural circles. The third part of the Paper refers to the traditionalist ideological positions that Kalajić consistently advocated as a kind of worldview for most of his life. The Traditionalist school, led by thinkers such as René Guénon, Frithjof Schuon, Julius Evola, and others, represents a distinct religious-philosophical school of thought in the 20th and 21st centuries whose basic guiding ideal is the existence of a common universal truth found in all major world religions. Kalajić’s first encounters with the writings of René Guénon began in his early youth in the artistic group "Mediala," where he was most likely introduced to Guénon’s writings by Miro Glavurtić. Kalajić’s education in Italy during the first half of the 1960s was crucial for the complete adoption of traditionalist positions, where he became thoroughly acquainted with all the leading traditionalist authors and their works, especially those of Julius Evola, the leading right-wing Italian traditionalist. The fourth part of the Paper shows how suitable this ideological and doctrinal worldview was for perceiving and understanding the potential of Russian society, the people, and its historical traditions to embark on the path of renewal and re-strengthening. The last part of the Paper provides concluding considerations on the extent of Kalajić’s assessments and predictions about the "Rising of Russia," which largely took place in accordance with what Dragoš Kalajić had predicted.